Effects of Elevated CO2 on Grain Yield and Quality in Different Wheat Cultivars - Yue Zhang; Chaoyong Kang; Shan Lin; Zaijun Yang; Yichao Wu; Shuhong Wei (Agronomy, 2025)
While the effects of elevated CO2 (eCO2) on crops have been extensively studied, cultivar-specific responses and impacts under higher CO2 concentrations (>800 μmol/mol) remain unclear. Here, we addressed these two aspects to reveal the effects of eCO2 (approximately 900 μmol/mol) on the yield and quality of three wheat cultivars, Chinese spring (CS), Chuanmai 44 and Neimai 9. The results indicated the net photosynthetic rate (Pn) and water use efficiency (WUEi) of the three cultivars significantly increased under 900 μmol/mol CO2 concentration. Elevated CO2 increased the hundred-grain weight (HGW) of Chuanmai 44 (+32.51%, p < 0.05) and Neimai 9 (+8.47% p < 0.05), but had little effect on HGW of CS. CO2 elevation significantly increased the N content in the grain of CS (+7.27%, p < 0.05). Elevated CO2 enhanced amino acid biosynthesis in CS but suppressed it in Chuanmai 44 and Neimai 9. No significant changes in grain mineral concentrations occurred in CS and Chuanmai 44 under eCO2 conditions. Neimai 9 demonstrated significant decreases in K and Mg, with non-significant reductions in other elements. The effects of eCO2 on grain yield and quality were closely linked to cultivars. This study will provide insights for understanding effects of CO2 concentration and cultivar interactions on crop growth and selecting wheat cultivar to cope with future climate change.